Developing real-time sonification with optical motion capture to convey balance-related metrics to dancers - Dahl, L.; Knowlton, C.; Zaferiou, A. (Proceedings of the 6th International Conference on Movement and Computing, 2019)
This paper presents initial efforts in developing and evaluating a system for real-time sonification of balance during dance and other dynamic real-world movements. The system uses marker-based motion capture to calculate multiple balance metrics, which are used to control the parameters of a sound-generating process. This allows dancers and choreographers to explore balance as a compositional element and has potential for specific applications to improve strategies for maintaining balance in clinical populations. Initial feasibility tests suggest that subjects engage in enjoyable explorations that cause them to move beyond their normal range of activities. These habit-breaking explorations point towards promising use of the sonification system as a choreographic tool for dancers.